Comparison of volatile composition and color attributes of mulberry wine fermented by different commercial yeasts. Issue 2 (26th July 2017) - Ouyang, Xiaoyu; Zhu, Baoqing; Liu, Ruojin; Gao, Qiong; Lin, Guo; Wu, Jiabao; Hu, Zeying; Zhang, Bolin
Abstract: This study investigated the volatile composition and color attributes of mulberry wine fermented by three yeast strains, including Red Fruit (RF), Red Vintage (RV), and ES488 (ES). Results showed different yeasts altered the physicochemical properties, volatile composition, and color attributes of the samples. The highest contents of total phenol and total anthocyanins were observed in ES wine and RF wine, respectively. Higher level on alcohols, terpenes, and benzenes together with lower concentration on carbonyl compounds was observed in RV wine. Esters were the most abundant volatiles, and the total esters' concentration was similar among these samples. The primary aroma in mulberry wine was floral and caramel flavors. The RV wine exhibited higher level on the fruity and chemical aromas. Additionally, the RV wine possessed higher brightness, lower red color, and color intensity. Color contribution from the copigmented and polymerized anthocyanins was significantly improved in RV wine and ES wine, respectively. Practical applications: Different yeast strains during mulberry wine fermentation played an important role in affecting the composition of volatiles and color attributes, which further determines the overall quality of mulberry wine. The findings from this study could provide useful reference on optimizing mulberry wine fermentation through selecting suitable yeast strains.